The effectiveness of motivational interviewing method in changing the dental and oral health behavior of pregnant women at RSIA Sitti Khadijah 1 Makassar: Efektivitas metode motivational interviewing terhadap perubahan perilaku kesehatan gigi dan mulut ibu hamil di RSIA Sitti Khadijah 1 Makassar - Rasmidar Samad; Ayub Irmadani Anwar; Fuad Husain Akbar; Annisa Rahmayani (Makassar Dental Journal PDGI Makassar, 2024)
The purpose of this study was to determine the effectiveness of motivational interviewing method on oral health behaviour of pregnant women. This study used a quasi-experimental method with a pretest and posttest design with control group with the subject of pregnant women at RSIA Sitti Khadijah 1 Makassar. Based on the results of the normality test with Shapiro Wilk, the data were not normally distributed, so the Wilcoxon test was used with the results of knowledge, attitudes and actions that were significantly different between the motivational interviewing group and dental health education with a value of p<0.05 (0.000) and the results of importance, interest, self-efficacy and perception were significantly different between the motivational interviewing group and dental health education with a value of p <0.05 (0.000). It is concluded that motivational interviewing is effective in changing the health behaviour of pregnant women at RSIA Sitti Khadijah 1 Makassar.